Danggui-Yimucao Herb Pair Can Protect Mice From the Immune Imbalance Caused by Medical Abortion and Stabilize the Level of Serum Metabolites - Bi, Shi-Jie; Yue, Shi-Jun; Bai, Xue; Feng, Li-Mei; Xu, Ding-Qiao; Fu, Rui-Jia; Zhang, Sai; Tang, Yu-Ping (Frontiers in Pharmacology, 2021)
Unintended pregnancy is a situation that every woman may encounter, and medical abortion is the first choice for women, but abortion often brings many sequelae. Angelica sinensis Radix (Danggui) and Leonuri Herba (Yimucao) are widely used in the treatment of gynecological diseases, which can regulate menstrual disorders, amenorrhea, dysmenorrhea, and promote blood circulation and remove blood stasis, but the mechanism for the treatment of abortion is not clear. We determined the ability of Danggui and Yimucao herb pair (DY) to regulate the Th1/ Th2 paradigm by detecting the level of progesterone in the serum and the expression of T-bet and GATA-3 in the spleen and uterus. Then, we detected the level of metabolites in the serum and enriched multiple metabolic pathways. The arachidonic acid pathway can directly regulate the differentiation of Th1/Th2 cells. This may be one of the potential mechanisms of DY in the treatment of abortion.